From engineering to aesthetics: morphology and constructive techniques of the New Bridge of Ronda (Spain) - Torres-Blanco, Daniel; Ladrón-de-Guevara-Muñoz, M. Carmen; Hidalgo-Fernández, Rafael Enrique (Journal of Architecture and Urbanism, 2025)
This study analyzes the morphology and construction techniques of the New Bridge of Ronda, focusing on its key engineering elements. Existing publications on the bridge’s construction history, along with research on stone bridge technologies, were used to identify elements in the New Bridge. The morphological characteristics and materials used were analyzed to deduce the techniques employed. The research shows that the New Bridge follows construction methods typical of stone bridges from Roman times, despite being built in the 18th century. Its height required large abutments and multi-level vaults, resembling medieval bridge designs, resulting in a unique structure compared to most stone bridges. This paper fills the gap in knowledge about the construction techniques and morphology of the New Bridge, offering a deeper understanding of its design. The value of this study lies in its contribution to the understanding of the New Bridge’s construction methods, shedding light on its historical significance and aiding in its preservation. This study enhances the appreciation of the New Bridge, supporting efforts for its preservation for future generations.